A proton-exchange membrane fuel cell and ultra-capacitor system model for stand-alone residential applications - Ibrahim Alhamrouni; Mohamed Salem; Awang Jusoh; Tole Sutikno (Universitas Ahmad Dahlan, 2022)
Energy consumption by sector in Malaysia is rising significantly, especially for residential and commercial sectors, and is expected to continue to increase in the upcoming years. The existing power generated from a proton-exchange membrane fuel cell (PEMFC) system may be insufficient to sustain peak load demands during peak periods in stationary residential applications. The presence of an ultra-capacitor (UC) bank would be beneficial as a support as it can supply a large burst of power. The integration of PEMFC and UC has the potential to provide an effective way to supply power demands, has better energy efficiency, and is also economically friendly. In this research, we demonstrate a proposed combined PEMFC and UC bank that operates in parallel. A novel design methodology and dynamic model for both PEMFC and UC systems as energy sources have been developed for stand-alone residential applications. The simulation results are shown in Matlab Simulink. These results are based on mathematical and dynamic models of the system being shown.